Representation and reality in Wittgenstein's Tractatus - Zalabardo, José L (O. U. P, 2015)
José L. Zalabardo puts forward an interpretation of central ideas in Wittgenstein's Tractatus Logico-Philosophicus concerning the structure of reality and our representations of it in thought and language.--